First record of Chordodes creplin, 1847 (Nematomorpha, Gordioidea) species from a hillstream of Bandarban, Bangladesh (Bangladesh Journal of Zoology, 2015)
Abstract not availableBangladesh J. Zool. 42(2): 301-303, 2014